L’accès ouvert est-il l’avenir des revues de recherche architecturale et urbaine ? - Béatrice Gaillard; Laurence Bizien; Véronique Cohoner (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
Since the first on line journals (early 1990s) and the use by researchers of open archives as a means of disseminating their research (late 1990), the evolution of journal publishing towards a digital, open mode has been underway and is gaining all scientific sectors, attracting the interest of researchers. Architecture, urban planning and landscape research journals are not immune to this digital transformation and the changes it induces, encouraged by institutions and funders. Some journals have already changed, and the movement seems irreversible, but reluctance remains. After presenting a state of the art of the resources available online and the active role of libraries in promoting this format of scientific dissemination, the present article takes stock of the conditions for setting up open access within the disciplines concerned: the importance of a support policy and the taking into account of economic issues, the sustainability of the staff working on their writing and dissemination infrastructures, the assurance of a reliable quality process in the face of the proliferation of preprints versus the requirements of funding organizations and the obstacles of the current model for evaluating researchers. Diversifying open access distribution models for architecture, urban planning and landscape journals could create a new dynamic, such as incubators, for regional journal portals or preprints platforms, for the benefit of sustainable and fair access to architectural research.